Political Da’wah Strategy of Islamic Parties in Indonesia - Ishaq, Ropingi El (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2022)
This study aims to map the problems and da’wah efforts in political fields that need to be done in Indonesia. The study uses qualitative analytical method. The data sources in this study come from books, research results, documents of political da’wah activities, and other literary sources gained from literary method and review. The data analysis is done using da’wah theory. The results of this study describe that Islamic da’wah in Indonesia faces some challenges, which are, firstly, facing the decline of society’s trusts towards political institutions. Consequently, the state leadership’s legitimacy decreases. Secondly, Indonesia is facing demographic bonus. Thirdly, in global context, there are threats of energy and food crisis, global warming, and others. Meanwhile, the political reality found in this study shows that various political approaches from each existing Islamic parties created obstacles in uniting steps and synergy in da’wah. Therefore, Islamic da’wah in political fields needs to be done by Islamic parties by doing various strategic political agendas. Firstly, it could be done by presenting strong legitimate leadership from society. Secondly, the strategy is by mapping the potential and problems as well as sharing roles and tasks among the existing state elements. Thirdly, it is by building a system that can unite the steps comprehensively in managing the state life. This da’wah needs to be done so that the state and nation life management runs systematically that could realize righteous and prosperous society’s life.